Проблемы лексикографического представления русской разговорной речи в толковом словаре - Krysin, Leonid (Wiener Slawistischer Almanach, 2022)
The article considers lexicographic features of contemporary everyday Russian speech and types of information. It uses examples from the Explanatory Dictionary of Russian Everyday Speech, which has been compiled under the supervision of the author of this article.